1997
DOI: 10.3109/01913129709023246
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and Morphometric Investigation of Human Brain Capillaries in Normal and Peritumoral Tissues

Abstract: Capillaries of peritumoral and normal brain tissues were ultrastructurally and morphometrically investigated to evaluate the changes in peritumoral capillaries connected with the tumor-associated vasogenic edema. The endothelial cells of peritumoral capillaries showed varying thickness, electron-lucent cytoplasm, and structurally normal tight junctions. The basal lamina was thickened, rarefied, and vacuolated. The pericytes were provided with pinocytotic vesicles and phagocytic bodies. The astrocytic glia appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(61 citation statements)
references
References 44 publications
1
59
0
1
Order By: Relevance
“…58 These components not only provide a mechanical supporting structure for the capillary wall, they are also important as a negatively charged barrier arising from the chondroitin and heparan sulfate residues, in addition to the anionic properties of the luminal and abluminal membranes of the endothelial cells. 59 Our results suggest that adsorptive-mediated endocytosis occurs at least at the luminal side of brain capillaries. The similarity in behavior observed for the peptide vectors studied suggests that the externalization at the abluminal side of endothelial cells may also be via a receptor-independent mechanism.…”
Section: Mechanism Of Brain Uptakementioning
confidence: 79%
“…58 These components not only provide a mechanical supporting structure for the capillary wall, they are also important as a negatively charged barrier arising from the chondroitin and heparan sulfate residues, in addition to the anionic properties of the luminal and abluminal membranes of the endothelial cells. 59 Our results suggest that adsorptive-mediated endocytosis occurs at least at the luminal side of brain capillaries. The similarity in behavior observed for the peptide vectors studied suggests that the externalization at the abluminal side of endothelial cells may also be via a receptor-independent mechanism.…”
Section: Mechanism Of Brain Uptakementioning
confidence: 79%
“…In semithin sections, vessels were seen as randomly oriented vascular pro les. ECs, some of which were relatively normal, exhibited the ultrastructural spectrum of nonspeci c abnormalities known to occur in capillaries of primary and metastatic CNS tumors (Bertossi et al, 1997;Shibata, 1989), which were observed in both the gliomas and lymphomas in our study sample. These included marked irregularity of lumen size, with blebs and vesicles being either partially attached or free-oating in occulent material containing cell debris.…”
Section: Morphology Of Capillary Endothelium: Nonspeci C Changesmentioning
confidence: 93%
“…7). Increased electron lucency, presumably due to activation of capillary ECs and pericytes and accompanied by an increase in abluminal endocytosis, has been observed in peritumoral regions of anaplastic gliomas (Bertossi et al, 1997).Our study is morphologic and descriptive. On that basis alone, the ECs of PCNSLs are distinctive and are different from the ECs of other brain tumors.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The peritumoral region of metastases represents vasogenic edema caused by increased interstitial water (60), in contrast to the peritumoral region of gliomas, which consists of tumoral infiltration into the brain parenchyma and accompanying neovascularity beyond the contrast-enhancing margins of the tumor (30). Due to the presence of these infiltrating tumor cells, peritumoral pMRI and sMRI of gliomas as compared to metastases show increased rCBV (1.3 Ïź 0.9 vs. 0.4 Ïź 0.2) and increased Cho (2.3 Ïź 1.2 vs. 0.8 Ïź 0.2) (19).…”
Section: Peritumoralmentioning
confidence: 99%